Air pollution in the area of operating siderite plant in Niná Slaná - Gešperová Dana; Brehuv Ján; Hančulák Jozef; Bobro Milan (Acta Montanistica Slovaca, 1999)
The dust deposition analyses the imission load in the area of Siderite Plant Niná Slaná has been carried out for tens of years. In the present time the observation of freshly fallen snow quality has begun to be realized with the aim to determine the collected pollutants in the snow. The pollutants have the municipal as well as the industrial origin. The range of plant emission by the chemical data processing and by their comparision with the dust deposition was investigated. Finally, the imission action of the plant on its wider surroundings was found out by this way.